On Distance (r,k)-Fibonacci Numbers and Their Combinatorial and Graph Interpretations - Dorota Bród (Journal of Applied Mathematics)
We introduce three new two-parameter generalizations of Fibonacci numbers. These generalizations are closely related to k-distance Fibonacci numbers introduced recently. We give combinatorial and graph interpretations of distance (r,k)-Fibonacci numbers. We also study some properties of these numbers.